เส้นทางการดำรงอยู่ของวงปีพาทย์พื้นเมืองในจังหวัตลำปาง - มณีทอง พรสวรรค์ (Community and Social Development Journal, 2013)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อสืบค้นประวัติความเป็นมา และจัดทำฐานข้อมูลวงปีพาทย์พื้นเมืองในจังหวัดลำปางเพื่อใช้เป็นแนวทางในการอนุรักษ์พีนฟูต่อไป โดยมีกลุ่มผูให้ข้อมูลหลัก จำนวน 9 คน ได้แก่ หัวหน้าวงดนตรี จำนวน 4 คน นักดนตรี จำนวน 5 คน และจากการศึกษาข้อมูลจากเอกสารที่เกี่ยวข้อง วิธีดำเนินการวิจัยใช้การสัมภาษณ์ การสนทนากลุ่ม ผลการวิจัยพบว่า วงปีพาทย์พื้นเมืองในจังหวัดลำปาง ได้รับการสืบทอดและรับอิทธิพลมาจากเมืองหริภุญไชย ได้มืการเปลี่ยนแปลงการประสมวงไปตามยุคสมัย การเปลี่ยนแปลงแต่ละครั้งมีเครื่องดนตรีที่ใช้เป็นหลักและจำเป็นต้องมี คือ ฆ้องวง แนหลวง ตะโพนมอญ และฉาบมอญ เนื่องจากเป็นสัญลักษณ์และรวมถึงการเป็นรัตลักษณ์ของวงปีพาทย์พื้นเมือง ปัจจุบันพบว่าวงปีพาทย์ พื้นเมืองในจังหวัดลำปางเหลือเพียง 16 วง ด้วยสาเหตุที่ค่าใช้จ่ายในการจ้างวงปีพาทย์พื้นเมืองไปบรรเลงมีราคาค่อนช้างแพงเฉลี่ย 6,000-8,000 บาทต่อครั้งต่อวง จึงเป็นเหตุให้ซาวบ้านหันไปใช้นวัตกรรมรันใหม่โดยใช้เครื่องแห้ง ซึ่งจะเป็นการเปิดเพลงบรรเลงพื้นเมืองผ่านเครื่องเสียงแทนการจ้างวงปีพาทย์พื้นเมืองมาบรรเลง สิ่งเหล่านี้เป็นค่านิยมใหม่เพราะมีราคาถูก ช่วยลดภาระในการเตรียมเวทีและการดูแลสมาซิกในวงของเจ้าภาพ จากประเด็นดังกล่าว ควรมีการสืบทอดวงปีพาทย์พื้นเมือง โดยจัดทำเป็นหลักสูตรท้องถิ่นและจัดทำเป็นวิชาเสือกให้แก่นักเรียน รวมถึงจัดตั้งวงปีพาทย์พื้นเมืองในโรงเรียนเพื่อให้บริการชุมชนแทนการเปิดเครื่องแห้ง สำหรับหน่วยงานที่เกี่ยวช้อง เห็นได้ว่าสภาวัฒนธรรมจังหวัดมีบทบาทสำคัญในการผลักดัน ล่งเสริม สนับสบุน และเผยแพร่การสืบทอดภูมิปัญญาท้องถิ่นวงปีพาทย์พื้นเมือง ซึ่งเป็นวงดนตรีที่มีความสำคัญในจังหวัดลำปางและใกล้จะสูญหาย A PATHWAY TO THE HISTORY OF VI’S LAvNNA ORCHESTRA The aim of this study is to retrieve the history of Lampang’s Lanna Orchestra and to organize the data base of Lampang’s Lanna Orchestra for the preservation guideline. The qualitative research was made by collecting data from 9 key informants; 4 band leaders and 5 musicians together with searching the related documents, interviewing and doing the focus group discussion. The results were as following: Lampang’s Lanna Orchestra was transferred and influenced from Haripunchai era which has been changed the style and performance according to each era. each change, the Lanna orchestra considers the main and important music instruments which are Gong, Nae Luang, Tapon Mon and Mon Cymbals according to the outstanding and symbolized features. Nowadays, there are only 16 Lampang’s Lanna Orchestra bands in Lampang. Because of the high expense which is about 6,000-8,000 per time, people use new innovation, the audio music, instead of live music performance. The new innovation is chosen because of its cheapness and helps in saving time for preparing the performance and taking care of musicians. According to the issue, Lampang’s Lanna Orchestra body of knowledge should be transferred in the form of local curriculum and through selective subject for students in schools to encourage students to perform as the public service instead of using the audio music. The provincial cultural council plays essential role in encouraging, supporting and publicizing Lampang’s Lanna Orchestra which it is considered the province local wisdom and almost disappeared from Lampang province.